Macroeconomics Determinations of Gold Price in United States - Seng, Ling Ngu; Kueh, Jerome Swee Hui (UNIMAS Publisher, Universiti Malaysia Sarawak, 2020)
Nowadays, gold prices have been volatile, and the wealth of gold investors depend on the movement of gold prices. The purpose of this study is to examine the relationship between gold prices, crude oil prices, inflation rate, real interest rate and stock prices in United States. This study uses monthly data covering the period ranging from January 1990 to August 2018. The Johansen and Juselius (JJ) Cointegration test and Vector Error Correction Model (VECM) are conducted in this study. The result shows that there is a long-run relationship among gold prices, crude oil prices, inflation rate, real interest rate and stock prices. The results show that inflation rate and crude oil prices are significance and positively related to gold prices, while stock prices and real interest rate are negatively affecting gold prices. There are three unidirectional Granger causality and one bidirectional Granger causality in the short run. Only inflation rate Granger cause gold price, which means that inflation rate directly affects the gold prices. This study allows community such as central bank, government, financial institution, economist, investor and policy makers in manipulating and controlling the movement of the gold prices so that they have a better decision making to diversify their risks.